Montreal Museum of Fine Arts, Collection of Mediterranean Antiquities, Vol. 3, The Metal Objects and the Gems : Musée des beaux-arts de Montréal, La collection des antiquités, Vol 3. Les objets en métal et les gemmes - Caron, Beaudoin,; Fossey, John M., (Monumenta Graeca et Romana, 2019)
This is the third out of eight projected volumes making available to the public the contents in the collection of Greek and Roman Antiquities in one of Canada's most prestigious museums. Here are presented a variety of metal objects (mostly bronze figurines, medical instruments, brooches, weaponry and a lead sarcophagus), the small collection of jewelry and the ancient gems and seal stones (mainly Roman) some still set in rings. Ce volume est le troisième de la série de huit volumes projetés qui vise à publier la collection des antiquités grecques et romaines d'un des grands musées canadiens. Nous présentons ici des objets métalliques très variés (surtout des statuettes de bronze, des instruments médicaux, des épingles, des armes et un sarcophage de plomb), un petit nombre de bijoux et de gemmes anciennes (surtout romaines) certaines encore serties dans une bague.